GUIDELINES RELATED TO PERFORMANCE RESTRICTIONS IN THE PRODUCT-SERVICE SYSTEM: A SYSTEM DYNAMICS APPROACH - Ariente Neto, Rafael; Forcellini, Fernando Antônio (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
The dynamic behavior of a Product-Service System is influenced by the delays regarding customer decisions and nonlinearities of perceptions. These factors can generate performance restrictions when services are added to products without managerial review, since System Dynamics models that address the Product-Service System do not provide a detailed description of the operational dynamics of services or the relationship of the system with customer perception. Thus, in this article a model is proposed to represent graphically the dynamic behavior of the service aggregation to deliver value. Using the System Dynamics methodology, the results included a conceptual model showing the main dynamic factors, a structural model and its mathematical description. This enables the contribution: the establishment of guidelines for management and product development process. Four guidelines are detailed highlighting the importance of considering the satisfied condition, the ease of the obtainment and consumption of value and the operational and control issues.